L'exploitation forestiere illegale en Indonesie: un inquietant processus de legalisation - Obidzinski, K.; Suramenggala, I.; Levang, P. (2001)
This article points to the importance of systems and praxis-oriented approach in understanding the problem of illegal logging in Indonesia. In recent years, there has been a tendency on the part of industry analysts and forestry sector observes to view the seemingly irremediable spread of illegal logging in the country in isolation, as a result of disassociated and pre mediated criminal acts. This paper proposes a different view of the problem. It suggests that illegal logging is not a simple criminal offense, but a complex system with multiple stakeholders at its base. It further argues that illegal logging is also a way for local people to get a share of the profits from logging, profits denied by the central government for the last thirty years. Recent developments, like the possibility for local government to grant small-scale concessions now enable illegal timber operators to conduct their business legally. As a result, local communities are courted by so-called investors who covet their forests. With the implementation of regional autonomy in Indonesia, local politicians also find it their interests to support small concessions. Recent attempts by the central government to control this new rush on forest have failed. Local governments are no longer willing to comply with the injunctions of the central government. The only way for the Ministry of Forestry to regain control (or at least to minimize unsustainable logging practices) would be to acknowledge this new paradigm and find a place for it within the overall forest policy. Long term solutions to the problem will probably involve a combination of community-based logging and joint-venture arrangements with industrial concessionaires.